Determinan Minat Berkarir Mahasiswa di Lembaga Keuangan Syariah Dengan Motivasi Sebagai Variabel Moderasi - Nur Latifah , Ramadhani; Setyono, Joko (Journal of Business Management and Islamic Banking, 2022)
Research Aims: This study aims to determine the influence of personality and market considerations work on student career interests in Islamic financial institutions with motivation as a moderating variable. Design/methodology/approach: The research method used is a quantitative method. Population this research is a student of Islamic banking UIN Sunan Kalijaga Yogyakarta with a sample of 146 people obtained by purposive sampling method. Data that used is primary data, using an online questionnaire/google form. Data that obtained were analyzed using the Partial Least Square (PLS) analysis technique through SmartPLS software. Research Findings: The results of the study indicate that there is a positive and significant effect of personality variables and labor market considerations on student career interests. Motivation able to moderate the relationship between labor market considerations and students' career interests. However, motivation is not able to moderate the relationship between personality and career interest student.